Reflections and trajectories for interdisciplinary research on the ecological transition - Cesare Sposito; Francesca Scalisi (Agathón)
AGATHÓN Volume 13 follows its predecessor on Innovability©® | Digital Transition and collects essays and research on Innovability©® | Ecological Transition, aware of its pressing relevance, but also of the scope suggested by the proposed dual key of interpretation. The published papers convey several reflections and research trajectories based on the need for a multiscalar nature of interventions, which guarantees effects that are induced to a broader environmental context than the one of reference, and for teams that address critical issues with a holistic and systemic inter- and transdisciplinary collaborative approach, in a sort of speciation of disciplines that modifies their traditional statutes; what emerges then is that the intangible and material tools we can deploy today are numerous also thanks to the possibilities offered by digital technologies in the different design, implementation and management phases of the process.